Navigating digital transformation challenges: The role of utilization and exploratory innovation in chinese logistics SMEs - Fuyuan Yang, Boonsub Panichakarn; Supavanee Thimthong (Decision Science Letters)
This study investigates the high-quality development of Chinese logistics SMEs by analyzing the effects of digital technology adoption, organizational resilience, utilization innovation, and exploratory innovation. It explores how digital transformation improves operational efficiency and adaptability, while assessing the mediating role of utilization innovation in connecting technology adoption and resilience to enterprise success. Additionally, the study examines the moderating effect of exploratory innovation on these relationships. A survey of 340 logistics professionals and SMEs within China's supply chain sector was conducted, with hypotheses tested using SPSS and SmartPLS-4. The results reveal that digital technology adoption and organizational resilience significantly contribute to enterprise development, with utilization innovation playing a pivotal mediating role. Furthermore, exploratory innovation moderates the relationship between digital adoption and innovation, highlighting the importance of adaptability in dynamic markets. This study presents a comprehensive framework integrating digital adoption, resilience, and innovation, offering valuable insights into how SMEs can address the challenges of digital transformation. Policymakers and industry stakeholders are encouraged to implement supportive policies, financial incentives, and technological investments to enhance the competitiveness of SMEs.